A pilot study using ecological momentary assessment via smartphone application to identify adolescent problematic internet use. (November 2020) - Gansner, Meredith; Nisenson, Melanie; Carson, Nicholas; Torous, John
Highlights: 62.5% of youth with psychiatric illness met problematic internet use criteria at one time point during the study period. Youth with problematic internet use may also have severe anxiety and depression. Episodes of problematic internet use relieve anxiety symptoms in short-term. Ecological momentary assessment may aid understanding of problematic internet use. Abstract: For some youth, pathologic Internet use can cause significant distress and dysfunction, a phenomenon known as Problematic Internet Use (PIU). PIU has been associated with poorer health outcomes in adolescents with existing psychiatric illness but understanding PIU has been challenging due to research methodologies using cross-sectional, self-report data. This study assessed the feasibility of using app-based ecological momentary assessment (EMA) to provide more ecologically-valid data to identify and characterize the relationship between mood symptoms and PIU in adolescents in active mental health treatment. 25 youth (aged 12–23) were recruited to use an EMA app for 6 weeks. 96% of participants completed the study and the majority of participants completed surveys at least once weekly. Youth with anxiety disorders endorsed significantly greater benefit from using the app to monitor PIU. While PIU severity was positively correlated with worsened anxiety and depression, analyses of the temporal relationships between PIU and mood symptoms showed that anxiety symptoms were significantly improved after episodes of PIU. Overall results suggest that app-based EMA may be both acceptable and feasible to understand PIU in this population. Follow-up studies should consider personalization of study protocols and use of digital phenotyping methodology to collect more objective measurements of behavior.